Scientific grounds for assessment of work of cutting tools on the analysis of acoustic characteristics of the manufactured and instrumental materials. - Буряк, А.В.; Буряк, В.Г. (Problems of Tribology, 2015)
The article examines closely related characteristics of the manufactured and tool materials on the stages of the control values of the main physical properties of out-of-process and active control of their changes in the process of cutting. The article focuses on substantiated facts of continuous acoustic oscillatory and wave processes on the microstructure of the tool material, leading to the accumulation of tension fatigue and fracture (wear) of the working part of the tool. For an unambiguous assessment of the characteristics of the energy state of the manufactured and tool materials with general parameters characterizing the oscillatory and wave processes in the stages of control out-of-process and in the process of machining, it is proposed to perform the synthesis of parameters using the theory of cause and effect link due to the accounting values of e, depending on the argument value that determines the end result of functional dependencies.